The Largest Subunit of Human RNA Polymerase III Is Closely Related to the Largest Subunit of Yeast and Trypanosome RNA Polymerase III - Sepehri, Setareh (Cold Spring Harbor Laboratory Press, 1997)
In both yeast and mammalian systems, considerable progress has been made toward the characterization of the transcription factors required for transcription by RNA polymerase III. However, whereas in yeast all of the RNA polymerase III subunits have been cloned, relatively little is known about the enzyme itself in higher eukaryotes. For example, no higher eukaryotic sequence corresponding to the largest RNA polymerase III subunit is available. Here we describe the isolation of cDNAs that encode the largest subunit of human RNA polymerase III, as suggested by the observations that (1) antibodies directed against the cloned protein immunoprecipitate an active enzyme whose sensitivity to different concentrations of α-amanitin is that expected for human RNA polymerase III; and (2) depletion of transcription extracts with the same antibodies results in inhibition of transcription from an RNA polymerase III, but not from an RNA polymerase II, promoter. Sequence comparisons reveal that regions conserved in the RNA polymerase I, II, and III largest subunits characterized so far are also conserved in the human RNA polymerase III sequence, and thus probably perform similar functions for the human RNA polymerase III enzyme. [The sequence data described in this paper have been submitted to the GenBank data library under accession no. AF021351.]